Scientific workflow management systems and workflow patterns. (11th May 2010) - Shiroor, Amruta; Springer, John; Hacker, Thomas; Marshall, Brandeis; , Jeffrey Brewer
Scientific workflow management systems primarily consist of data flow oriented execution models, and consequently, these systems provide a limited number of control flow constructs that are represented in dissimilar ways across different scientific workflow systems. This is a problem, since the exploratory nature of scientific analysis requires the workflows to dynamically adapt to external events and control execution of different workflow components. Hence some degree of control flow is necessary. The lack of standard specifications for specifying control flow constructs in scientific workflow management systems leads to workflows designed using custom developed components with almost no reusability. In this paper, we present a standard set of control flow constructs for scientific workflow management systems using workflow patterns. Firstly we compare the control flow constructs present in three scientific workflow management systems: Kepler, Taverna and Triana. Secondly these patterns are implemented in the form of a template library in Kepler. Finally, we demonstrate the use of this template library to design scientific workflows.